Impaired Nitric Oxide Mediated Vasodilation In The Peripheral Circulation In The R6/2 Mouse Model Of Huntington’s Disease - Kane, Andrew D. (Sci Rep, 2016)
Recent evidence shows that the Huntington’s disease (HD) extends beyond the nervous system to other sites, including the cardiovascular system. Further, the cardiovascular pathology pre-dates neurological decline, however the mechanisms involved remain unclear. We investigated in the R6/2 mouse model of HD nitric oxide (NO) dependent and independent endothelial mechanisms. Femoral artery reactivity was determined by wire myography in wild type (WT) and R6/2 mice at 12 and 16 weeks of adulthood. WT mice showed increased endothelial relaxation between 12 and 16 weeks (R(max): 72 ± 7% vs. 97 ± 13%, P < 0.05). In contrast, R6/2 mice showed enhanced endothelial relaxation already by 12 weeks (R(max) at 12w: 72 ± 7% vs. 94 ± 5%, WT vs. R6/2, P < 0.05) that declined by 16 weeks compared with WT mice (R(max) at 16w: 97 ± 13% vs. 68 ± 7%, WT vs. R6/2, P < 0.05). In WT mice, the increase in femoral relaxation between 12 and 16 weeks was due to enhanced NO dependent mechanisms. By 16 weeks of adult age, the R6/2 mouse developed overt endothelial dysfunction due to an inability to increase NO dependent vasodilation. The data add to the growing literature of non-neural manifestations of HD and implicate NO depletion as a key mechanism underlying the HD pathophysiology in the peripheral vasculature.